Addiction as degradation of life - Beran, Ondřej (Trinity International University, 2019)
The paper discusses equivocations involved in the concept of addiction and suggests its understanding in terms of one's (degraded) way of leading one's whole life. I argue against common conceptions of addiction, identifying its core either in a physiological (substance-induced) condition of craving or in weakness of will as insufficient. Using Fingarette's notion of “central activity,” I explore addiction as a peculiar kind of central interest, pervading and predating on one's other interests and characterized by a corrosion of a sense of temporality and responsibility. Since addiction is a response to events in the addict's life (a personally specific lack of healthy sources of positive reinforcement), therapy-consisting in reestablishment of the capacity of navigating responsibly one's activities and interests-must proceed in a way that takes the particular aspects of each case into account.
Addiction as degradation of life
Keywords: addiction; will; central activity; degradation; reinforcement; závislost; vůle; degradace; posílení